Ponciá Vicêncio: narrative and colonial counter-memory - Miranda, Fernanda Rodrigues de (2019)
The paper is composed of three parts. In the first, I draw some parallels between Conceição Evaristo's work Ponciá Vicêncio, comparing to other novels by brazilian black authors, signaling the contiguity of a dispersed, but communicating, set of novels that are interspersed by the romanesque genre and by the authorship of black women – as the pioneer Úrsula, of Maria Firmina dos Reis, published in the nineteenth century; Água funda (1946), by Ruth Guimarães, the first novel by a black author published after the end of slavery; Pedaços da fome (1963) and Diário de  Bitita (1986), both of Carolina Maria de Jesus; As mulheres de Tijucopapo (1982), Marilene Felinto and Um defeito de cor (2006), by Ana Maria Gonçalves. In a second moment, I approach the concept of “escrevivência”, observing its borderline location between fiction, realism and autobiography, emphasizing that the critical invoice of the concept generates an amplification of its respective scope. Finally, I highlight some lines of strength of the work, in order to emphasize its narrative power to forge and make visible the colonial counter-memories of the nation.